Emergence of Human Economics and the Contour of Future HRD - Barman, Arup (Prabandhan: Indian Journal of Management, 2010)
Theories of material economics have ruled HRD for a quite long term. Till today, there are numerous researches, reviews on economics as a basis for HRD theories (i.e. under neo-classical economics) those generated models pertinent to HRD research. It is argued that institutional economics theories do not provide any foundation in furthering theories of future HRD. New economics such as humane economics, inclusive capitalism are in the path of evolution, and are demanding a fresh look over subjects such as micro, meso, macro HRD. The article addresses how emerging human economics and inclusive capitalism would have more implications to contemporary HRD theories, research, and practices that would restyle the future HRD.